2016
DOI: 10.1016/j.ihj.2015.08.022
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of congenital heart disease in rural population of Himachal – A population-based study

Abstract: Prevalence of CHD in general population was 6.3/1000. ASD was the commonest lesion. CHD was more common in female.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
23
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 11 publications
6
23
1
Order By: Relevance
“…These results are in accordance with studies in Gorgan, northern Iran [17], South distract in Iran [20] Rwanda [4], and Xinjiang in China [21]. The study was done in India presented ASD was the commonest lesion followed by VSD similar to our study [18]. While another study presented VSD was the commonest (39.5%) then followed by ASD, PS, and PDA [22] also the study was carried out in Southwestern of Iran reported the commonest types were VSD (28.47%), ASD (10.39%) and TOF (9.3%) [13].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These results are in accordance with studies in Gorgan, northern Iran [17], South distract in Iran [20] Rwanda [4], and Xinjiang in China [21]. The study was done in India presented ASD was the commonest lesion followed by VSD similar to our study [18]. While another study presented VSD was the commonest (39.5%) then followed by ASD, PS, and PDA [22] also the study was carried out in Southwestern of Iran reported the commonest types were VSD (28.47%), ASD (10.39%) and TOF (9.3%) [13].…”
Section: Discussionsupporting
confidence: 93%
“…Several studies estimate the incidence of CHD is 4 up to 10 cases per 1000 live births [6,16]. A study from Iran have reported higher CHD incidence 8.6 per 1000 live births [17], another from China reports an overall CHD of 8.2 per 1000 total live births [14] and a study from India reports a lower incidence of 3.9 per 1000 live births but still higher than our study [18]. The lower incidence of CHD in our study may be due to lack proper checking and follow-up for all live births resulting in missed cases at birth and early neonatal period.…”
Section: Discussioncontrasting
confidence: 58%
“…10 Females were slightly more affected in this study with male to female ratio of 0.9:1 which is similar to studies done in different parts of the world. 11 Further we have observed that girls with RHD are slightly younger than boys, similar to observation made by Shrestha et al where RHD was commoner in girls and affecting them at a younger age. 3 The median duration of symptoms among new cases was 1 year (range, 1 week to 9 years) with one child had symptoms for as long as nine years without seeking any health care facilities.…”
Section: Discussionsupporting
confidence: 91%
“…Mandal S et al 17 reported that males had a higher (13.5%) prevalence of IHD than females (9.4%) (P> 0.05). Similar reports were given by Bhardwaj R et al 21 and Murthy PD et al 19 The age wise prevalence of CHD among males was also high when age wise prevalence of compared to females. (p = 0.01).…”
supporting
confidence: 81%